IMPLEMENTASI BUDIKDAMBER PADA LAHAN SEMPIT DENGAN AKUAPONIK DI KELURAHAN BANJAR AGUNG KECAMATAN CIPOCOK JAYA KOTA SERANG - Holilah; Rizky Andaresa; Nur Fadhilah Al Hadiana; Lina Herlina; Adelia Tri Oktaviani; Adelia Masnapita; Andi Santoso; Yeyet Kurniasih (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2023)
The level of population density in Banjar Agung Village, Cipocok Jaya District, Serang City is 1,369.47 People/Km2. The problem of narrow land is a problem that is often experienced by residents in residential areas, including in the Banjar Agung village, especially in the village of Bogeg RW 02 which is a partner in this community service. During the Covid-19 pandemic, food and economic security issues are serious issues that need attention. Seeing these phenomena and problems, the purpose of this activity is to get a fish cultivation system in small media and does not require large land, it is economical, the media is easy to obtain and the technology can be done by everyone. This activity is expected to be a solution to overcome the problem of narrow land but can support food security and the community's economy. The method used is the delivery of materials, the practice of making budikdamber, and evaluation of training activities. The results of the implementation of this activity are catfish farming in 60 liter buckets with maintenance for 30 days producing SR 40-67% harvested biomass reaching 2420gr with an average weight per head of 68.74gr, kale produced as many as 30 bunches and residents of Bogeg RW village 02 is very enthusiastic in budikdamber activities with aquaponics so that it helps in maintaining food security and improving the economy during the pandemic.  ---  Tingkat kepadatan penduduk di Kelurahan Banjar Agung kecamatan Cipocok Jaya Kota Serang sebesar 1.369,47 Jiwa/Km2. Permasalahan lahan sempit merupakan permasalahan yang seringkali dialami oleh warga di pemukiman penduduk tak terkecuali di kelurahan Banjar Agung, khususnya di kampung Bogeg RW 02 yang merupakan mitra dalam pengabdian masyarakat ini. Di masa pandemi Covid-19 ini, masalah ketahanan pangan dan ekonomi menjadi masalah serius yang perlu diperhatikan. Melihat fenomena dan permasalahan tersebut tujuan dari kegiatan ini untuk mendapatkan sistem budidaya ikan dalam media kecil dan tidak memerlukan lahan yang luas, ekonomis, medianya mudah didapatkan dan teknologi yang bisa dilakukan oleh semua orang. kegiatan ini diharapkan mampu menjadi solusi untuk mengatasi permasalahan lahan sempit tetapi dapat mendukung ketahanan pangan dan perekonomian masyarakat. Metode yang digunakan adalah penyampaian materi, praktik pembuatan budikdamber, serta evaluasi kegiatan pelatihan. Hasil dari pelaksanaan kegiatan ini adalah budidaya ikan lele dalam ember 60 liter dengan pemeliharaan selama 30 hari menghasilkan SR 40-67% biomassa panen mencapai 2420gr dengan berat rata-rata per ekor 68,74gr, kangkung yang dihasilkan sebanyak 30 tandan dan warga kampung Bogeg RW 02 sangat antusias dalam kegiatan budikdamber dengan akuaponik sehingga membantu dalam menjaga ketahanan pangan dan meningkatkan perekonomian dimasa pandemik.